Anaerobic Digestion of Olive Mill Wastewater and Process Derivatives—Biomethane Potential, Operation of a Continuous Fixed Bed Digester, and Germination Index - Jonas Pluschke; Katharina Faßlrinner; Fatma Hadrich; Slim Loukil; Mohamed Chamkha; Sven-Uwe Geißen; Sami Sayadi (Applied Sciences, 2023)
Olive mill wastewater (OMW) management is an economic and environmental challenge for olive oil-producing countries. The recovery of components with high added value, such as antioxidants, is a highly researched approach that could help refinance performant wastewater treatment systems. Anaerobic (co-)digestion is a suitable process to valorize the energetic and nutritional content of OMW and OMW-derived waste streams from resource recovery processes. Issues of process stability, operation, and yields discourage industrial application. Deepening the understanding of biomethane potential, continuous anaerobic digester operational parameters, and co-substrates is key to large-scale implementation. The biomethane potential of different OMW-derived samples and organic solid market waste as co-substrate was 106–350 NL methane per kg volatile solids (VS). The highest yields were obtained with the co-substrate and depolyphenolized OMW mixed with retentate from an ultrafiltration pretreatment. Over 150 days, an anaerobic fixed-bed 300 L digester was operated with different OMW-derived substrates, including OMW with selectively reduced polyphenol concentrations. Different combinations of organic loading rate and hydraulic retention time were set. The biogas yields ranged from 0.97 to 0.99 L of biogas per g of volatile solids (VS) eliminated, with an average methane content in the produced biogas of 64%. Potential inhibition of the process due to high polyphenol concentrations or over-acidification through volatile fatty acids was avoided in the continuous process through process and substrate manipulation. High concentrations of potassium and low concentrations of nitrogen and phosphate end up in the digestate. Sulfate reduction results in high H2S concentrations in the biogas. The digestate was tested for phytotoxic properties via the germination index. Diluted digestate samples improved germination by up to 50%.